1997
DOI: 10.1111/1523-1747.ep12292144
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Exposure Depletes Vitamin E and Induces Lipid Peroxidation in Murine Stratum Corneum

Abstract: The presence of ozone (O(3)) in photochemical smog is an important health concern. We hypothesized that the stratum corneum (SC), as the outermost skin layer and the permeability barrier of the skin, represents a sensitive target for O(3)-induced oxidative stress. To test this hypothesis, SKH-1 hairless mice were anesthetized and exposed for 2 h to O(3) by using two strategies: (i) single exposures to 0 (n = 12), 1 (n = 4), 5 (n = 4), and 10 (n = 4) ppm; and (ii) repeated daily exposures to 0 ppm (controls; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 29 publications
7
91
0
4
Order By: Relevance
“…This conclusion is supported by the product analysis reported above (further details, including estimated yields, are in SI Text) and stands in contrast to earlier reports that have focused on vitamin E and other less abundant antioxidants as ozone scavengers (14-16) and malondialdehyde as a prominent ozonolysis product (14).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This conclusion is supported by the product analysis reported above (further details, including estimated yields, are in SI Text) and stands in contrast to earlier reports that have focused on vitamin E and other less abundant antioxidants as ozone scavengers (14-16) and malondialdehyde as a prominent ozonolysis product (14).…”
Section: Resultssupporting
confidence: 78%
“…The single most abundant ozone-reactive constituent is squalene [10 to 12% of the surface lipids (13)]. Other "antioxidants" present in the stratum corneum can react with ozone, including ascorbic acid (vitamin C), tocopherols and tocotrienols (vitamin E), cholesterol, ubiquinones (coenzyme Q), glutathione, and uric acid (14)(15)(16). However, these are much less abundant than squalene and unsaturated fatty acid moieties in their free or esterified forms (17).…”
mentioning
confidence: 99%
“…Thiele et al 17,34 have reported the presence of vitamin E in the epidermis and SC and that sebaceous secretion is a major mechanism for its delivery to the skin surface. Exposure to UVA, UVB and ozone results in reduction of vitamin E. 34,35 Gerloczy et al 36,37 first reported vitamin E in vernix over 40 years ago at amounts from trace levels to 90 mg/g wet weight (0.21 mmole/g wet weight), comparable to levels in high vitamin E organs.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Exposure to UVA, UVB and ozone results in reduction of vitamin E. 34,35 Gerloczy et al 36,37 first reported vitamin E in vernix over 40 years ago at amounts from trace levels to 90 mg/g wet weight (0.21 mmole/g wet weight), comparable to levels in high vitamin E organs. We found a mean vitamin E content of 13.2 to 18.9 mg/g wet weight of vernix (0.031 to 0.044 mmole/g wet weight).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…The cytotoxicity of ozone is due to its capability of antioxidant depletion [63][64][65] and its interaction with unsaturated lipids to generate damaging free radicals or toxic intermediate products [66]. Ozone exposure can influence antioxidant levels and oxidation markers in the outermost stratum corneum layer [67,68].…”
Section: Pollution and Its Effect On The Skinmentioning
confidence: 99%